Optimizing the regulation and control of sports injury and fatigue of Winter Olympic ice and snow athletes based on injury prevention - Ye, L.; Di, P. (Revista Brasileira de Medicina do Esporte, 2021)
This study reveals the characteristics and relationship of sports injury and fatigue of the Winter Olympics athletes, and monitors the athletes` psychological condition through case analysis of excellent athletes, and provides empirical evidence for athletes` psychological training and preparation for the physical and mental health services of Winter Olympics. Through questionnaires, literature review and other methods to study the injury situation of Winter Olympics ice and snow athletes, the results show that the proportion of chronic lumbar and knee joint injuries, and repeated muscle strains of Chinese Winter Olympics ice and snow athletes is large, and the cure rate is not high. The preparation activities are neither paid enough attention or sufficient, and the rationality of training plan arrangement is insufficient. The main cause of injury is insufficient understanding of the mechanism of injury and illness among athletes and coaches. Individual elite athletes need to improve their coping skills and pay attention to their psychological fatigue. In view of the sports` psychological characteristics and the problems faced by winter athletes, personalized psychological intervention programs should be formulated.